299. D-dimer as an ICU Admission Risk Predictor in COVID-19 Patients, A Prospective Study. (4th December 2021) - Narváez - Ramírez, Oriana; Morales-Cely, Lina; Bustos-Moya, Ingrid G; Fuentes-Barreiro, Yuli Viviana; Lozada-Arciniegas, Julian; Ibañez-Prada, Elsa Daniela; Bravo-Castelo, Laura A; Parra-Tanoux, Daniela; Ramirez, Paula; Gomez-Duque, Salome; Gamboa-Silva, Enrique; Caceres, Edar; et al.
Abstract: Background: Since the onset of the 2019 coronavirus disease 2019 (COVID-19) pandemic, the rapid increase in community-acquired pneumonia (CAP) cases has led to an excessive rate of intensive care units (ICU) admissions, a rate varying between 5-18%, depending on the country. Consequently, the study of serum biomarkers, such as D-dimer, have been utilized to identify patient with severe disease. However, further data is needed to confirm the association between this serum concentration of D-dimer and the risk of ICU admission. Thus, the aim of this study was to determine if serum concentration of D-dimer predict the risk of ICU admission in patients with COVID-19 and CAP. Methods: A prospective observational study was carried out at the Clinica Universidad de La Sabana, Colombia. Patients older than 18 years old, hospitalized for COVID-19 or CAP were included. Then, patients were stratified into ICU and non-ICU patients. Plasma samples were collected within the first 24 hours of hospital admission to quantify D-dimer using the PATHFAST system. Concentrations were compared among groups and to assess the biomarker capacity to predict ICU admission risk, ROC curves were used. Finally, a DeLong test was applied to compare their differences. Results: A total of 240 patients diagnosed with lower respiratory tract infection were included in the study. 88 patients were COVID-19 negative (CAP) and 152 were positive. Plasma concentrations of D-dimer (µg/ml) were significantly higher in COVID-19 patients admitted to the ICU when compared with non-ICU COVID-19 admitted patients (Median [IQR]; 1.54 [0.9-3.25] Vs. 1.13 [0.69-1.69], p=0.005). The area under curve (AUC) ROC to predict ICU admission was 0.62 among COVID-19 patients. DeLong's test p value was 0.24. Serum D-dimer an ICU admission Conclusion: D-dimer seems to be a promising tool to identify COVID-19 patients with disease. However, this predicting capacity was not observed in CAP patients. Further studies are needed to identify the mechanisms underling the elevation of D-dimer in COVID-19 patients. Disclosures: All Authors : No reported disclosures